Efektivitas Peraturan Pemerintah Republik Indonesia Nomor 2 Tahun 2003 dalam Penegakan Kode Etik Profesi Polri di Satuan Brimob Polda Sumatera Utara - Universitas Muslim Nusantara Al Washliyah, Echo Agung Wichaksono; Herlina Hanum (Albayan Journal of Islam and Muslim Societies, 2024)
This study aims to analyze the effectiveness of the implementation of Government Regulation of the Republic of Indonesia Number 2 of 2003 on the Disciplinary Regulations of Police Officers in the enforcement of the Indonesian National Police Professional Code of Ethics (KEPP) within the Brimob Unit of the North Sumatra Regional Police. Employing a qualitative approach with normative-empirical design, data were collected through interviews, observations, and document analysis. The findings demonstrate the regulation’s effective enforcement, indicated by a yearly decrease in disciplinary violations. Nonetheless, implementation is challenged by the limited number of accredited personnel and the procedural requirement that disciplinary hearings be conducted at the provincial police headquarters. These findings highlight the necessity for capacity-building and structural reforms within the police institution to ensure just and efficient discipline enforcement